Delirium prevalence, interventions and barriers in intensive care units in German-speaking countries: a retrospective cross-sectional secondary analysis - Exl, Matthias Thomas; Fischbacher, Sibylle; Lindroth, Heidi; Liu, Keibun; Hoffmann, Magdalena; Jeitziner, Marie-Madlen; Nydahl, Peter; Haken, Rebecca von; Krüger, Lars; Schimböck, Florian (Nursing in critical care, 2025)
Background The prevalence of delirium in intensive care units (ICUs) is high and has a major impact on patient outcomes. Aim To describe delirium assessment instruments, prevalence, interventions and barriers in delirium management in adult and paediatric ICUs; and to explore the association between delirium prevalence and reported interventions and barriers at unit level. Study Design A secondary analysis of the cross-sectional World Delirium Awareness Day Delirium Survey on 15 March 2023. This was a prospective study to assess the one-day point delirium prevalence, practices and quality improvement efforts across healthcare systems. Data was analysed descriptively and using multiple linear regression. Results Data of 1612 assessments in 123 ICUs from three German-speaking countries were analysed. The most frequently used delirium assessment instrument was the Intensive Care Delirium Screening Checklist (43.9%, n = 54). The prevalence of delirium at 8 AM was 18.6% and at 8 PM 20.4% from the 94 ICUs included in the regression analyses. Prevalence for adult and paediatric and mixed ICUs are comparable. Main reported over all unit-level interventions were ‘pain management’ (95.9%, n = 118), ‘mobilization’ (94.3%, n = 116) and ‘verbal re-orientation’ (84.6%, n = 104). Main reported over all unit-level barriers were ‘shortage of staff’ (53.7%, n = 66) and ‘patients who are difficult to assess’ (44.7%, n = 55). Interventions such as ‘avoidance of bladder tubes/catheters’ in all ICUs, ‘use of ear plugs and/or sleep glasses’ in adult ICUs and ‘mobilization’ in paediatric and mixed ICUs were associated with reduced delirium prevalence. Across all ICUs, as well as in both adult and paediatric ICUs, ‘lack of appropriate scores for delirium assessment’ was identified as a significant barrier. Conclusions One fifth of assessed ICU patients suffer from delirium. Several reported unit-level interventions and barriers may have an impact on delirium prevalence, suggesting an approach for future studies and clinical practice. Relevance to Clinical Practice In clinical practice, unit-level ‘avoidance of bladder tubes/catheters’, ‘use of ear plugs and/or sleep glasses’ and ‘mobilization’ may be used as delirium prevention and treatment interventions.